PENGELOLAAN DANA ZAKAT DALAM UPAYA PEMBERDAYAAN DAN KEMANDIRIAN YATIM DHUAFA’ (STUDI KASUS DI LAZNAS YATIM MANDIRI PUSAT SURABAYA) - Titin Saidah; Norma Rosyidah (STAI AN-NAJAH INDONESIA MANDIRI, 2020)
Zakat is one the five pillars of Islam Which every moeslim should practice. Managing zakat funds as capital for business empowerment or education and improving the mustahik economy, so that Yatim Dhuafa’ can run or pay for life consistenly without depending on others and the Yatim Mandiri National Amil Zakat Institute is one for the institutions that manages zakat funds and the empowerment and independence of the Orphans and Dhuafa’ at the Yatim Mandiri National Zakat Institute. This study uses descriptive qualitative research methods, using interview techniques, observation, documentation and data analysis. The Purpose of this research is to find out how the management and zakat in the efforts of empowerment and independence of orphants carried out by the National Yatim Mandiri Amil Zakat Institute Surabaya Center. Trough the analysisi above, the result of this study are two research findings: First, How to manage zakat funds for empowering orphans of the orphaned by the Yatim Mandiri Laznas requires good and effective management so that it can be distributed evenly. Second, the role of the empowerment and independence program for Orphans and Dhuafa’ at Laznas Yatim Mandiri provides significant changes for them. So that they are more creative, innovative, work hard and more independent and do not depend on their parents anymore. Keywords: Zakat, Yatim Dhuafa’, and Empowerment.